Trends and Future Challenges in Sampling the Deep Terrestrial Biosphere - Wilkins, Michael J.; Daly, Rebecca; Mouser, Paula J.; Trexler, Ryan; Wrighton, Kelly C.; Sharma, Shikha; Cole, David R.; Biddle, Jennifer F.; Denis, Elizabeth; Fredrickson, Jim K.; Kieft, Thomas L.; Onstott, Tullis C.; et al. (Frontiers in Microbiology, 2014)
Research in the deep terrestrial biosphere is driven by interest in novel biodiversity and metabolisms, biogeochemical cycling, and the impact of human activities on this ecosystem. As this interest continues to grow, it is important to ensure that when subsurface investigations are proposed, materials recovered from the subsurface are sampled and preserved in an appropriate manner to limit contamination and ensure preservation of accurate microbial, geochemical, and mineralogical signatures. On February 20th, 2014, a workshop on “Trends and Future Challenges in Sampling The Deep Subsurface” was coordinated in Columbus, Ohio by The Ohio State University and West Virginia University faculty, and sponsored by The Ohio State University and the Sloan Foundation’s Deep Carbon Observatory. The workshop aims were to identify and develop best practices for the collection, preservation, and analysis of terrestrial deep rock samples. This document summarizes the information shared during this workshop.